2014
DOI: 10.3389/fnana.2014.00148
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent expression of neuronal PAS domain-containing protein 4 (npas4a) in the developing zebrafish brain

Abstract: In rodents, the Npas4 gene has recently been identified as being an important regulator of synaptic plasticity and memory. Homologs of Npas4 have been found in invertebrate species though their functions appear to be too divergent for them to be studied as a proxy for the mammalian proteins. The aim of this study, therefore, was to ascertain the suitability of the zebrafish as a model organism for investigating the function of Npas4 genes. We show here that the expression and regulation of the zebrafish Npas4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 76 publications
(109 reference statements)
4
11
0
Order By: Relevance
“…The olfactory system exhibited robust expression, shortly after birth, with other brain areas following thereafter. A similar expression pattern has been described in other vertebrate species including the developing zebrafish brain (Klarić et al, 2014 ) GABAergic and glutamatergic.…”
Section: Discussionsupporting
confidence: 78%
“…The olfactory system exhibited robust expression, shortly after birth, with other brain areas following thereafter. A similar expression pattern has been described in other vertebrate species including the developing zebrafish brain (Klarić et al, 2014 ) GABAergic and glutamatergic.…”
Section: Discussionsupporting
confidence: 78%
“…S4B). Murine NPAS4 is known to regulate synaptic function (Spiegel et al, 2014), and npas4a expression has previously been described to be restricted to the zebrafish brain, similar to mammalian Npas4 (Klaric et al, 2014). We have previously reported that npas4l is expressed specifically in the LPM during early somitogenesis using in situ hybridization (Reischauer et al, 2016).…”
Section: Transcriptomic and Epigenomic Analyses Of Npas4l Mutantsmentioning
confidence: 87%
“…In human, the NPAS4 transcript was mainly expressed in brain tissue, though, unlike in rodents, no expression was observed in the testis [ 5 ]. This brain-specific expression pattern seems to be conserved even in lower vertebrates as demonstrated by our recent study which showed that, in the adult zebrafish, the expression of the zebrafish Npas4 homolog npas4a was also restricted to the brain [ 42 ].…”
Section: Expression Of Npas4mentioning
confidence: 99%